2012
DOI: 10.3109/03639045.2012.729594
|View full text |Cite
|
Sign up to set email alerts
|

Powdered self-emulsified lipid formulations of meloxicam as solid dosage forms for oral administration

Abstract: The objectives of this study were to prepare a powdered self-emulsified (SEDDS) formulation of meloxicam and to compare its oral bioavailability against commercial Mobic tablets. The SEDDS formulation was prepared by in situ salt formation of meloxicam in a blend of lipid excipients and aqueous tris (hydroxymethyl) aminomethane solution. The liquid SEDDS was subsequently adsorbed on silica powder and was tested for size, flow, and crystal growth. The flowability index of the powdered SEDDS was borderline accep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 23 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…The formulations were then kept for 48 hours while being visually inspected for turbidity and phase separation before droplet size distribution tests were performed. 8 …”
Section: Methodsmentioning
confidence: 99%
“…The formulations were then kept for 48 hours while being visually inspected for turbidity and phase separation before droplet size distribution tests were performed. 8 …”
Section: Methodsmentioning
confidence: 99%
“…The formulations were then kept for 48 hours while being visually inspected for turbidity and phase separation before droplet size distribution tests were performed. 8 In vitro evaluation of the prepared MLX liquid SMEDDS Thermodynamic stability studies Numerous thermodynamic stability tests (centrifugation, heating-cooling cycle, and freeze-thaw cycle) were done on all the prepared liquid SMEDDS formulations to determine the effect of centrifugation and temperature on the stability of self-microemulsions and to avoid selecting metastable formulations for further development and characterization. 9…”
Section: Saturation Solubility Studiesmentioning
confidence: 99%
“…Nevertheless, the release out of liquid su-SEDDS due to heat or physical stress during storage can be degrade the quality of final product; thus, the physico-chemical stability of hard capsule dosage form should be monitored during storage. Considering probability of this stability issue, the stability study of solid SEDDSs with meloxicam in gelatin and HPMC capsules were conducted [241]. It was shown that the extent of capsule deformation was dependent on the filled material and the low water and propylene glycol content affected shell deformation less.…”
Section: Hard Capsulesmentioning
confidence: 99%